2017
DOI: 10.1016/j.omtm.2017.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Improved MECP2 Gene Therapy Extends the Survival of MeCP2-Null Mice without Apparent Toxicity after Intracisternal Delivery

Abstract: Intravenous administration of adeno-associated virus serotype 9 (AAV9)/hMECP2 has been shown to extend the lifespan of Mecp2−/y mice, but this delivery route induces liver toxicity in wild-type (WT) mice. To reduce peripheral transgene expression, we explored the safety and efficacy of AAV9/hMECP2 injected into the cisterna magna (ICM). AAV9/hMECP2 (1 × 1012 viral genomes [vg]; ICM) extended Mecp2−/y survival but aggravated hindlimb clasping and abnormal gait phenotypes. In WT mice, 1 × 1012 vg of AAV9/hMECP2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
69
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(71 citation statements)
references
References 36 publications
2
69
0
Order By: Relevance
“…However, some challenges are still being overcome, such as toxicity from overexpression or mistargeting of the gene, packaging limitations of the viral vectors and limited brain transduction efficiency (Gadalla et al, 2017;Katz et al, 2016). In this study, we demonstrate intracellular delivery of the MeCP2 protein into neurons.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…However, some challenges are still being overcome, such as toxicity from overexpression or mistargeting of the gene, packaging limitations of the viral vectors and limited brain transduction efficiency (Gadalla et al, 2017;Katz et al, 2016). In this study, we demonstrate intracellular delivery of the MeCP2 protein into neurons.…”
Section: Discussionmentioning
confidence: 90%
“…It is characterized by apparently normal early development followed by profound neurologic regression around 1-2 years of age (Carrette et al, 2018;Katz et al, 2016). Since 2007, several gene therapy studies in rodents have shown that expression of functional MeCP2 can reverse the symptoms of Rett syndrome, even after disease onset (Gadalla et al, 2013(Gadalla et al, , 2017Guy, Gan, Selfridge, Cobb, & 385 Bird, 2007;Katz et al, 2016). Furthermore, exclusive MeCP2 expression in the CNS is sufficient to rescue the majority of Rett syndrome phenotypes (Ross et al, 2016), supporting the therapeutic potential of MeCP2 delivery to the CNS.…”
Section: Discussionmentioning
confidence: 99%
“…MeCP2 pathological mutations result in primarily a neurological phenotype characterized, in females, by regression of speech and purposeful hand motions, and the appearance of seizures, and respiratory abnormalities [24]. MeCP2 is expressed in most, if not all, neurons and glia [25][26][27][28][29], and previous studies have indicated that these cells can be targeted throughout the brain and spinal cord by adenoassociated virus 9 (AAV9) for facile analyses [30][31][32][33][34]. Importantly, a database of mutations causing Rett syndrome [35] indicates that 36% are caused by G>A mutations or C>T mutations that create opal stop codons, raising the possibility that adenosine deamination in these contexts may repair MeCP2 protein function.…”
Section: Introductionmentioning
confidence: 99%
“…At the cellular level, neural cells in Rett male and female mice have smaller somas, nuclei, and reduced process complexities (10)(11)(12)(13)(14)(15)(16), reminiscent of affected human cells (17)(18)(19)(20). Importantly, restoration of MeCP2 in Mecp2-null mice, via conditional Cre recombinase (21) or gene therapy approaches (22)(23)(24)(25), reverses many of the Rett-like symptoms and cellular deficits, even in late stages of the disease. The phenotype reversals suggest that in humans, RTT may be amenable to gene replacement strategies (14,(22)(23)(24)(25).…”
mentioning
confidence: 99%
“…Importantly, restoration of MeCP2 in Mecp2-null mice, via conditional Cre recombinase (21) or gene therapy approaches (22)(23)(24)(25), reverses many of the Rett-like symptoms and cellular deficits, even in late stages of the disease. The phenotype reversals suggest that in humans, RTT may be amenable to gene replacement strategies (14,(22)(23)(24)(25). However, duplications spanning the MECP2 gene in humans result in MECP2 overexpression and a severe neurological disorder (26).…”
mentioning
confidence: 99%